Development And Validation Of A Blended Learning Guitar Pedagogy Module For Pre-Service Music Teachers In Thailand - Boonyanant, Klen (2024)
Guitar is a great musical instrument for teaching in schools since it provides various benefits for children. Pre-service music teachers majoring in guitar in thailand should be proficient in guitar pedagogy in order to offer their students the greatest possible learning experience. A blended learning approach provides advantages to improve the quality of the guitar pedagogy course through a combination of online and face-to-face instruction. This study aims to develop, validate, implement, and test the efficacy of a blended learning guitar pedagogy module for pre-service music teachers in thailand. The module was created based on the addie model of instructional design, with the use of a mixed-method research methodology to collect both quantitative and qualitative data. The needs analysis survey of pre-service music teachers and guitar instructors revealed the content and structure of the module. Subject-matter experts validated the module using the delphi technique. Pre-service music teachers’ competencies in guitar pedagogy were measured based on the tpack framework for teacher education. Feedback and comments from pre-service music teachers and guitar instructors were examined to indicate the usefulness of the blended learning guitar pedagogy module.